2006
DOI: 10.1093/scan/nsl014
|View full text |Cite
|
Sign up to set email alerts
|

The Kuleshov Effect: the influence of contextual framing on emotional attributions

Abstract: Filmmakers have long recognized the importance of editing techniques to guide the audiences' perceptions and enhance the impact of a scene. We demonstrate behaviorally that pairing identical faces with either neutral or emotionally salient contextual movies, an editing technique referred to as the 'Kuleshov Effect', results in both altered attributions of facial expression and mental-state. Using functional neuroimaging (fMRI), we show that faces paired with emotional movies enhance BOLD responses in the bilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
130
1
16

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(160 citation statements)
references
References 68 publications
13
130
1
16
Order By: Relevance
“…We propose that ISC may be of use to both film theorists and the film industry by providing a quantitative, neuroscientific assessment of viewers' engagement with a film. ISC is only one example of a growing trend in neuroscience to study the human brain under a more realistic and natural setting (Bartels andZeki 2004a, 2004b;Haxby et al 2001;Mobbs et al 2006;Spiers andMaguire 2007a, 2007b;Wilson, Molnar-Szakacs, and Iacoboni 2007;Zacks et al 2001;Zeki 1998). These and other studies may provide the emerging field of neurocinematics with new tools for studying different aspects of films and filmmaking.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We propose that ISC may be of use to both film theorists and the film industry by providing a quantitative, neuroscientific assessment of viewers' engagement with a film. ISC is only one example of a growing trend in neuroscience to study the human brain under a more realistic and natural setting (Bartels andZeki 2004a, 2004b;Haxby et al 2001;Mobbs et al 2006;Spiers andMaguire 2007a, 2007b;Wilson, Molnar-Szakacs, and Iacoboni 2007;Zacks et al 2001;Zeki 1998). These and other studies may provide the emerging field of neurocinematics with new tools for studying different aspects of films and filmmaking.…”
Section: Resultsmentioning
confidence: 99%
“…Although the exact functions of these brain regions are still under investigation, such intermediate temporal coherency may be necessary for visual and cognitive processing functions that require integration of information across events. An example might be the processing of different kinds of montage relationships between adjacent shots (Eisenstein 1925; see also Mobbs et al 2006). Finally, processing over a long temporal scale (ranging from around 30 seconds to the entire movie sequence in our experiments) was needed to achieve high correlation across repeated presentations in more anterior regions of the brain that are believed to perform more complex, cognitive functions.…”
Section: From Single Shots To Juxtaposition Of Shots To Coherent Movimentioning
confidence: 99%
“…Recent evidence indicates that the natural context plays an important role in determining how facial and also bodily expressions of emotion are processed and reacted to [1][2][3][4][5][6][7][8][9][10][11][12][13]. A facial expression is recognized faster when presented in a congruent emotional background (for example, a fearful face in a threatening context) [9].…”
Section: Introductionmentioning
confidence: 99%
“…The few studies that have used functional magnetic resonance imaging (fMRI) to investigate the effect of affective context information on one or another stimulus category (faces, bodies, scenes) reported that the presence of affective information influences activity in the relevant category representation in the ventral stream, that is in the fusiform face area (FFA), the extrastriate body area (EBA), and the parahippocampal place area (PPA) [2,6,7]. The standard view is that the amygdala (AMG) is the central structure in orchestrating such up or down modulation [10,13,14]. For example, when a neutral face is seen in a threatening context, increased activation is observed in the FFA [6].…”
Section: Introductionmentioning
confidence: 99%
“…Yet the Kuleshov “effect,” if it exists at all in this three‐shot format, does so only under extremely circumscribed conditions (Barratt, Cabak Rédei, Innes‐Ker, & van de Weijer, 2016; Calbi et al., 2017; Mobbs et al., 2006; Prince & Hensley, 1992). Hochberg and Brooks (1996, p. 265) explained why: “Despite Eisenstein's (1949) assertion that two pieces of film of any kind, when placed in juxtaposition, inevitably combine into a new concept of quality, there is no reason to believe that without specific effort at construal by the viewer anything other than a meaningless flight of visual fragments … will be perceived.” In other words, the filmmakers must first win over the viewer to the narrative and the diegetic world before any mind reading will link the separate shots (see also Cutting, 2005).…”
Section: Discussionmentioning
confidence: 99%